Design and Fabrication of Slotted Multimode Interference Devices for Chemical and Biological Sensing. (14th June 2009) - Mayeh, M.; Viegas, J.; Srinivasan, P.; Marques, P.; Santos, J. L.; Johnson, E. G.; Farahi, F.
Abstract : We present optical sensors based on slotted multimode interference waveguides. The sensor can be tuned to highest sensitivity in the refractive index ranges necessary to detect protein-based molecules or other water-soluble chemical or biological materials. The material of choice is low-loss silicon oxynitride (SiON) which is highly stable to the reactivity with biological agents and processing chemicals. Sensors made with this technology are suited to high volume manufacturing.